Cost Reduction and Design Improvement of Hand Mixer for Baking Using Design for Manufacture and Assembly (DFMA) - Mohamed, Faiz Hakimi; Azli Nawawi, (Progress in Engineering Application and Technology, 2022)
In a competitive market, a product must deliver high performance at low cost. To design a new and improved product, use Design for Manufacture and Assembly (DFMA). This thesis emphasizes the benefits of applying DFMA to a product. The DFMA method simplifies and lowers the cost of the original design. The study used manual DFA calculation on the chosen product, a hand mixer. The manual Design for Assembly (DFA) methodology was used to explain the hand mixer DFMA application. The study's methodology was explained, as was the manual DFA analysis of design efficiency. The original hand mixer design had a 293.54s operation time and a RM115.76 operation cost. The improved design hand mixer efficiency was 60%, saving RM89.23 and 223.08 seconds in cost and operation time. The original hand mixer design efficiency was 46%. The new hand mixer design increased design efficiency by 30.43 percent. The manual DFA methodology was used to compare the original and improved efficiency design performance.